PENGARUH KARAKTERISTIK WIRAUSAHA DAN KREATIVITAS WIRAUSAHA TERHADAP KEBERHASILAN USAHA - Laia, Erika Elfianis (Jurnal Ilmiah Mahasiswa Nias Selatan, 2025)
The purpose of this study is to ascertain the impact of entrepreneurial traits as well as entrepreneurial creativity on business success (Empirical Study of Vegetable Traders in Teluk Dalam District). Quantitative research is the method employed. The data source used is a data source from vegetable traders, so The entire population of Telukdalam District vegetable sellers is the study's population. Questionnaires were distributed to respondents, namely at vegetable vendors in the Telukdalam District, as part of the data collection method. Multiple linear analysis is the data analysis technique used. The study's findings indicate that entrepreneurial traits and inventiveness have an impact on business success. Furthermore, in this research, a multiple linear regression equation was obtained, namely: Y= 9.210+0.495X1+0.307X2, which means that the Constant value (a)= 9.210 shows the constant value of business success when the value of entrepreneurial characteristics and entrepreneurial creativity is equal to zero. The regression coefficient of entrepreneurial characteristics (X1)= 0.495 shows that the value of entrepreneurial characteristics when it increases by 1 unit will increase business success by 0.495. The regression coefficient of entrepreneurial creativity (X2)= 0.307 shows that the value of entrepreneurial creativity when it increases by 1 unit will increase success business is 0.307. The conclusion from this research is that entrepreneurial characteristics and entrepreneurial creativity influence the business success of vegetable traders in Telukdalam District.